Pembelajaran Sex Education dengan Berbagai Media Pembelajaran pada Siswa TK Aisyiyah 1 Tidung - Angriawan, Randy; B, Angelin Marici; Takaya, Stefany Marici; Ilyas, Salsabila Ayu Qhairunnisa; Kastro, Yohanes Angelo; Nuralisa, St; Nurzaenab, Nurzaenab Angelo; Mashud, Mashud; Awaliah, Neneng; Sabir, Fitriana M; Syamsu, Suryadi (LESTARI : Jurnal Pengabdian Kepada Masyarakat, 2024)
The golden age of early childhood is a critical period for establishing a foundation in intellectual and health understanding, including sex education. According to Article 28 Paragraph 1 of Law Number 20 of 2003 concerning the National Education System, sex education for young children is crucial for advancing the intellectual development of the younger generation. However, observations at Aisyiyah Kindergarten in Makassar City revealed that sex education had never been provided, resulting in a lack of understanding among students. To address this issue, a Community Service activity was conducted at Aisyiyah Kindergarten using robotics-based learning technology, including robot voices, songs, images in PowerPoint format, and teaching books. This program aims to enhance students' knowledge and understanding of sex education through interactive and enjoyable learning methods. Pre-test results showed only 24.4% correct answers from 18 participants, while post-test results after five days of learning showed a significant increase to 88.2% correct answers from 22 participants. These results indicate that the use of robotics technology in education can effectively increase students' learning interest and understanding. This program is expected to serve as a learning model that can be applied in various early childhood education institutions to improve the quality of education and children's understanding in the aspect of sex education